LEASING, LEASING TRANSACTION, LEASING OPERATING - Correia, Caetano Carceres; Kamaluddin, Kamaluddin (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
To find out the development of the business world, the more companies that enter the business world, the more funds and capital needs that must be fulfilled by various companies. This encourages the business industry that is engaged in financing, called financing institutions, especially leasing financing. The occurrence of the leasing transaction was motivated by insufficient funds from the lessee to purchase capital goods, so that he contacted the lessor to finance it. Based on qualitative research on leasing as a reference for further research, and secondly. As a follow-up research by looking at the existing novelty. The method used is descriptive analysis with a normative juridical approach. The research phase uses literature research with Secondary data and field studies with primary data. This data collection was obtained by means of literature research and also interviews obtained by means of field studies. Furthermore, the data were analysed using the juridical-qualitative method. "Therefore, financing activities are in the form of providing capital goods either on a lease basis with option rights or finance leases or without option rights or operating leases to be used by the lessee (user) for a certain period of time based on periodic payments until the end of the contract period, the lessee can purchase the goods, with the remaining value agreed by the lessor.